Building Resilience to Enhance Food and Nutrition Security, Incomes and Health in Northern Uganda (BRENU). Training module 1: Basic nutrition concepts curriculum and facilitators’ guide - Owori, Moses; Ecii, Juliet; Opus, David; Akullo, Jacqueline; Kato, Fred; Nabuuma, Deborah; Ekesa, Beatrice (2022)
Background This Training Manual on the Basic Concepts of Nutrition has been adapted from the Training Manual For Field Extension Service Providers, developed by Beatrice Ekesa, Deborah Nabuuma, Samalie Namukose and George Upenytho, by The Alliance of Bioversity International and CIAT, and used in the context of Building Resilience to Enhance Food and Nutrition Security, Incomes and Health in Northern Uganda (BRENU), an Action of the Development Initiative for Northern Uganda (DINU), a Government of Uganda programme implemented by International Institute of Tropical Agriculture (IITA) together with a consortium of five co-implementers namely: i) Volunteer Effort Development Concerns (VEDCO); ii) the Alliance of Bioversity International and CIAT (ABC); iii) Ernest Cook Ultra Sound Research and Education Institute (ECUREI); iv) Kilimo Trust and v) Rikolto International , supported by the European Union and supervised by the Office of the Prime Minister. As part of the consortium, ABC is responsible for conducting capacity building on nutrition for 2050 extension service providers representing 51,250 smallholder households. This training manual is part of a nutrition-sensitive package of formal training, informal technical assistance and mentoring services.